Endophyte-mediated effects on the growth and physiology of Achnatherum sibiricum are conditional on both N and P availability. - Xia Li (Public Library of Science (PLoS), 2012)
The interaction of endophyte-grass associations are conditional on nitrogen (N) availability, but the reported responses of these associations to N are inconsistent. We hypothesized that this inconsistency is caused, at least in part, by phosphorus (P) availability. In this experiment, we compared the performance of endophyte-infected (EI) and endophyte-free (EF) Achnatherum sibiricum subjected to four treatments comprising a factorial combination of two levels of N (N+ vs. N-, i.e. N supply vs. N deficiency) and two levels of P (P+ vs. P-, i.e. P supply vs. P deficiency) availability. The results showed that A. sibiricum-Neotyphodium associations were conditional on both N and P availability, but more conditional on N than P. Under N+P- conditions, endophyte infection significantly improved acid phosphatase activity of EI plants, such that the biomass of EI plants was not affected by P deficiency (i.e. similar growth to N+P+ conditions), and resulted in more biomass in EI than EF plants. Under N-P+ conditions, biomass of both EI and EF decreased compared with N+P+; however, EI biomass decreased slowly by decreasing leaf N concentration more rapidly but allocating higher fractions of N to photosynthetic machinery compared with EF plants. This change of N allocation not only improved photosynthetic ability of EI plants but also significantly increased their biomass. Under N-P- conditions, EI plants allocated higher fractions of N to photosynthesis and had greater P concentrations in roots, but there was no significant difference in biomass between EI and EF plants. Our results support the hypothesis that endophyte-grass interactions are dependent on both N and P availability. However, we did not find a clear cost of endophyte infection in A. sibiricum.